TANTANGAN DAN PELUANG PENGELOLAAN SEKOLAH ISLAM TERPADU - Muhamad Ihsan Fadhilah; Mas Enong Fatonah; A. Yani (Al Naqdu, 2025)
The management of Integrated Islamic Schools (SIT) faces significant challenges and opportunities in the context of modern education. The main challenges include high operational costs, strict government regulations, and changing social dynamics. In addition, the integration of general and religious curricula is often a complex issue that affects the quality of education. However, SIT also offers interesting opportunities, such as the increasing public interest in integrated education that emphasizes Islamic values. This holistic education concept is increasingly becoming a priority, especially among parents who want comprehensive education for their children. By implementing total quality management, SIT can increase competitiveness and attract more students, while also contributing positively to the development of students' character and morals